2011
DOI: 10.2147/opth.s21161
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of intravitreal human placental stem cell implants in inhibiting progression of diabetic retinopathy in type 2 diabetes: neuroprotective growth factors in the vitreous

Abstract: Background:Intravitreal injection of human mesenchymal stem cells has been shown to be effective in slowing the progression of diabetic retinopathy in an animal model of chemically induced diabetes mellitus. We studied changes in growth factor levels released from human mesenchymal stem cells in the vitreous cavity as well as changes in growth factor levels in host retinal neurons following intravitreal injection.Methods:Twenty-two Lewis rats were treated with an intravitreal human mesenchymal stem cell microi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…[ 66 ] Although DR is one of the most important visually debilitating diseases, only one ongoing clinical trial is targeting DR. [ 67 ] This may be due to the low number of experimental studies conducted in this specific area. Though several studies have pointed to various beneficial effects of stem cells in DR, [ 17 , 52 , 68 – 70 ] the present study demonstrates a detailed ERG analysis, specifically an improvement in OP waves.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…[ 66 ] Although DR is one of the most important visually debilitating diseases, only one ongoing clinical trial is targeting DR. [ 67 ] This may be due to the low number of experimental studies conducted in this specific area. Though several studies have pointed to various beneficial effects of stem cells in DR, [ 17 , 52 , 68 – 70 ] the present study demonstrates a detailed ERG analysis, specifically an improvement in OP waves.…”
Section: Discussionmentioning
confidence: 53%
“…[ 50 , 51 ] It has also been demonstrated that BMSC can increase the retinal and intravitreal concentrations of neuroprotective growth factors. [ 52 ]…”
Section: Discussionmentioning
confidence: 99%
“…In this animal model, the intravitreal administration of MSCs provides trophic support to the damaged tissue, and increased RGC survival [ 21 ]. Additionally, Yu et al reported that intravitreal MSC transplantation was neuroprotective after episcleral vein ligature, which can cause moderate ocular hypertension and RGC loss [ 54 ], and the same neuroprotective factors were also elevated in the vitreous cavity after the intravitreal administration of human placental stem cells in an animal model of DR [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A single intravitreal injection of placental-derived MSCs into diabetic rats has also resulted in a significant decrease in retinal cell apoptosis, such effect being related to increased intravitreal concentration of several neuroprotective growth factors [103].…”
Section: Msc-related Therapy For Diabetic Retinopathymentioning
confidence: 99%